Analysis of long-term results of surgical treatment of patients with a closed fracture of the patella using a new method - G. P. Kotel'nikov; Yu. D. Kim; D. S. Shitikov; I. O. Grankin; N. E. Likholatov; D. D. Sedenkova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The purpose of the study was to analyze the long-term results of surgical treatment of patients with a patella fracture, in the treatment of which a new method of osteosynthesis was applied.Materials and methods. The long-term results of surgical treatment of 18 patients with a closed patella fracture were analyzed, the functional state of the knee joint was assessed after 12 months from the operation using clinical and radiological methods. A clinical example of a patient with a traumatic closed fracture of the patella is given, illustrating the surgical treatment of this patient. The results of treatment are presented.Results. The data obtained indicate the effectiveness and biomechanical validity of the patented method. The prospects for further research are outlined.